The Early Middle Ages to 1300 - Crocker, Richard; Hiley, David (Oxford New York Oxford University Press, 1990)
Drawing on the work of leading British and American scholars, this revised volume presents an informed, timely picture of music from the fourth through the fourteenth century A.D. It begins with a discussion of Christian chant in the Mediterranean and goes on to cover Gregorian chant, liturgical drama, medieval song, instrumental music, and early polyphony down to the monumental organa composed at the cathedral of Notre Dame in the twelfth century. The new edition has been revised to incorporate the wealth of new research on early music done since Hughes's first edition was published in 1954, and includes over 200 musical examples and an exhaustive bibliography.
Keywords: Middle Ages (500-1400); Music history; Europe